Mapping seasonal sentiments of people visiting blue spaces in urban wetlands: A pilot study on inland cities of China - Li, Yanjiao; Sun, Yuxiang; Zhao, Yan; Wang, Yang; Cheng, Shiping (Frontiers in Ecology and Evolution, 2022)
To evoke positive human emotions is a critical goal of blue spaces in urban wetland parks. However, information is still scarce on how people self-express across the spatiotemporal spectrum when they come across wetlands which include varying levels of elevation in a single landscape and microclimate. In this study, 30 urban wetland parks were selected from 17 cities in Central China, where a total of 1,184 portrait photos of visitors were obtained from a social media platform (Sina Weibo) to analyze their expressed sentiments by rating facial expression scores of happy and sad emotions and net positive emotion index (NPE; happy-score minus sad-score) in 2020. Landscape metrics were remotely evaluated for every wetland park, and microclimatic factors were obtained for the days when the photos were taken. Based on regressions of park-level data, blue-space areas could be perceived as a positive driver to trigger happiness in spring (regression coefficient [RC] of 0.20), but it triggered negative emotions in autumn (RC of −2.98). The higher elevation areas triggered positive emotions in summer and autumn (RC of 1.35 × 10−3), but extreme daily temperature, air humidity, and wind velocity together triggered sadness (RC of 0.11, 0.03, and 0.51, respectively). Mapped distribution of the area and corresponding emotions showed that visiting blue space evoked more smiles in wetland parks of northern Hunan, southern Hubei, and eastern Anhui in spring. Blue spaces in Shanxi and northwestern Hebei evoked better moods in autumn. Smaller blue spaces in wetlands located at higher elevations were recommended for nature enthusiasts in warm seasons to overcome the prevalent sadness characteristic of that time of the year and location.